A CONFORMITY ANALYSIS OF THE USE OF ANTIRETROVIRAL (ARV) DRUGS IN HIV/AIDS PATIENTS WITH NATIONAL GUIDELINES IN HOSPITALS X YEAR 2022 – 2023 - Putri, Gusti Agung Ayu Adinda Fidelia Tresna; Ernawati, Desak Ketut; Ernawati, Desak Ketut; Satriyasa, Bagus Komang; Dewi, Ni Wayan Sucindra (E-Jurnal Medika Udayana; Vol 14 No 4 (2025): E-Jurnal Medika UdayanaDO - 10.24843/MU.2025.V14.i4.P04, 2025)
HIV/AIDS treatment using Antiretroviral (ARV) therapy aims to prevent HIV-related morbidity and mortality. ARV treatment must be carried out according to applicable national guidelines so that optimal therapeutic success can be achieved. The purpose of this study was to provide an overview of the conformity of ARV drug use in HIV/AIDS patients with the National Guidelines for Medical Services for HIV Management at Hospital X in 2022 – 2023. This study was a descriptive study with a retrospective data collection method by looking at the medical records of HIV/AIDS patients at Hospital X in 2022 – 2023. The research sample consisted of 57 patients using a total sampling technique. Data analysis used univariate analysis. The results of the study of 57 HIV/AIDS patients at Hospital X were dominated by male patients with 35 patients (61.4%). The most dominant age group was the 30 – 39 year old age group with a total of 18 patients (31,6%). The most widely used drug combination was a combination of Tenofovir + Lamivudine + Efavirenz with 33 patients (57.9%). The dose of the drug used was once a day as much as one tablet. Most patients had an advanced clinical stage, stage IV with 24 patients (42.1%). From the 57 medical record data obtained, the results showed that there was a conformity of the use of ARV drugs with the National Guidelines for Medical Services for HIV Management. This study showed that all HIV/AIDS patients who received ARV therapy at Hospital X in 2022 – 2023 were in accordance with the National Guidelines for Medical Services for HIV Management. Keywords: antiretroviral, conformity of drug use, HIV/AIDS, hospital, national guideline